Assessing the Impact of Business Closures on COVID-19 Outcomes - Peng, Xuequan Elsie (IMF Working Papers; Working Paper, 2022)
In this paper, we present a framework for assessing the effectiveness of different business closure policies, using New York City as a case study. Business closure policies have been widely implemented in an attempt to slow down the pandemic, but it is difficult to measure the contribution of closures of specific industries to virus transmission. Our framework allows us to estimate the impact of specific industry closures on the spread of COVID-19 via their effects on aggregate mobility. We find that early reopening led to a prolonged pandemic and a large case surge in the second wave during 2020, though the reopening allowed the city to regain its economic function as a consumption hub. An alternative policy that extends the lockdown is found to be more cost-effective as it makes future traveling safer and prevents the economy from relapsing into a more stringent policy regime.